2022
DOI: 10.1093/hr/uhac172
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH1-DTX35/DFR module regulates pollen fertility by promoting flavonoid biosynthesis in Capsicum annuum L.

Abstract: High pollen fertility can ensure the yield and efficiency of breeding work, but factors that affect the fertility of pepper pollen have not been studied extensively. In this work, we screened the reduced pollen fertility 1 (rpf1) mutant with reduced pollen fertility and yellow anthers from an EMS-mutagenized pepper population. Through construction of an F2 population, followed by BSA mapping and KASP genotyping, we identified CabHLH1 as a candidate gene for control of this trait. A G→A mutation at a splice acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Also present near this SNP is a gene with a myb-related protein 305-like function ( AsparagusV1_10.1876 ). These myb-related genes are usually involved in response to abiotic stresses, as in Vigna unguiculata , where a myb-related protein 305-like gene has been found to be upregulated after exposure to salt stress ( Zhang et al., 2022 ); however, they can also be associated with fruit production, as in Vigna mungo , where a myb-related protein 305-like gene has been found to be associated with a quantitative trait locus (QTL) for yield ( Singh et al., 2022 ), or with the ability to produce giant (mammoth) fruits, as in Cucurbita maxima ( Reddy et al., 2022 ). Therefore, it could be reasonable to assume that they may also be involved in determining flowering time and not solely in fruit characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Also present near this SNP is a gene with a myb-related protein 305-like function ( AsparagusV1_10.1876 ). These myb-related genes are usually involved in response to abiotic stresses, as in Vigna unguiculata , where a myb-related protein 305-like gene has been found to be upregulated after exposure to salt stress ( Zhang et al., 2022 ); however, they can also be associated with fruit production, as in Vigna mungo , where a myb-related protein 305-like gene has been found to be associated with a quantitative trait locus (QTL) for yield ( Singh et al., 2022 ), or with the ability to produce giant (mammoth) fruits, as in Cucurbita maxima ( Reddy et al., 2022 ). Therefore, it could be reasonable to assume that they may also be involved in determining flowering time and not solely in fruit characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Several structural genes of anthocyanin biosynthesis, including CHS, CHI, F3H, F3'5'H, DFR, ANS and UFGT, was basically conserved in most plants [43,45,46]. In recent years, an increasing number of reports suggested that avonoids are closely related to pollen fertility [32,44,[47][48][49].…”
Section: Diversity and Conservation Of Cawd40s Protein In Peppermentioning
confidence: 99%
“…Pepper, as a typical spicy vegetable, belong to the genus Capsicum of of the Solanaceae family and originated in South and Central America [30]. The Capsicum species have various morphological characteristics and several pepper species lack anthocyanins [17,31,32]. In recent years, several genes controlling anthocyanin synthesis have been identi ed in pepper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids comprise more than 9000 compounds and constitute a substantial category of plant secondary metabolites [ 18 ]. They have diverse biological functions in the growth and development of plants, including improving pollen fertility, imparting color, and influencing seed dormancy and germination [ 19 , 20 ]. In addition, flavonoids have protective roles against biotic and abiotic stresses, such as pathogen infections, ultraviolet (UV)-B, cold, drought, and salinity [ 21–23 ].…”
Section: Introductionmentioning
confidence: 99%